1992
DOI: 10.1111/j.2042-3306.1992.tb04776.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feeding schedule on the absorption of orally administered flunixin in the horse

Abstract: Summary The effects of access to hay and of restricted feeding on the pharmacokinetics of flunixin administered orally to six healthy ponies were compared in a cross‐over study. No access to feed for a few hours before and after flunixin administration resulted in rapid absorption with a mean peak plasma concentration of 2.84 ± 0.28 μg/ml attained in an average time of 0.76 ± 0.18 h, followed by an exponential decline in plasma concentration. A lower peak plasma concentration was obtained when ponies had free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 13 publications
(8 reference statements)
1
19
0
Order By: Relevance
“…phenylbutazone and meclofenamate, in vitro binding to hay and pony nuts was high (>98%) and binding to digesta in vivo was also demonstrated (Lees et al, 1988). In other in vivo studies it was shown that binding to feed and digesta influenced the pattern of absorption of phenylbutazone and flunixin and was postulated to be the cause of: (i) delayed absorption; and (ii) two or more peaks in the plasma concentration-time profiles (Maitho et al, 1986;Welsh et al, 1992).…”
Section: Influence Of Feed On Drug Bioavailabilitymentioning
confidence: 96%
See 1 more Smart Citation
“…phenylbutazone and meclofenamate, in vitro binding to hay and pony nuts was high (>98%) and binding to digesta in vivo was also demonstrated (Lees et al, 1988). In other in vivo studies it was shown that binding to feed and digesta influenced the pattern of absorption of phenylbutazone and flunixin and was postulated to be the cause of: (i) delayed absorption; and (ii) two or more peaks in the plasma concentration-time profiles (Maitho et al, 1986;Welsh et al, 1992).…”
Section: Influence Of Feed On Drug Bioavailabilitymentioning
confidence: 96%
“…In other in vivo studies it was shown that binding to feed and digesta influenced the pattern of absorption of phenylbutazone and flunixin and was postulated to be the cause of: (i) delayed absorption; and (ii) two or more peaks in the plasma concentration‐time profiles (Maitho et al. , 1986; Welsh et al. , 1992).…”
Section: Influence Of Feed On Drug Bioavailabilitymentioning
confidence: 99%
“…Horses that had ad libitum access to hay following the oral administration of 238 flunixin had a slower absorption of flunixin and a lower Cmax (Welsh et al 1992). Although 239 concentrations of flunixin in plasma were maintained for longer when animals had access to food 240 compared with when they were fasted (Welsh et al 1992). The AUC was not significantly 241 different between fasted and non-fasted animals with suggesting that the overall concentration of 242 flunixin absorbed is not affected by fasting.…”
mentioning
confidence: 88%
“…It is probable that our higher AUC was due to the 232 higher dose rate used in our study. 233 The pharmacokinetics of orally administered flunixin has been studied in goats (Königsson et al 234 2003), horses (Pellegrini-Masini et al 2004;Welsh et al 1992) and cattle (Odensvik 1995). 235 Following oral administration in the absence of feed in these species, flunixin is absorbed rapidly 236 and concentrations can still be detected up to 30 h after administration (Königsson et al 2003; 237 Odensvik 1995).…”
Section: Palatabilitymentioning
confidence: 99%
See 1 more Smart Citation